1973
DOI: 10.1103/physrevlett.30.594
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic Generation and Parametric Excitation of Waves in a Laser-Created Plasma

Abstract: ond, the short-time dynamics of all the simple fluids over remarkably large ranges of density and temperature are quantitatively described by Eq. (1) which should serve as an important benchmark for theories of the dynamics of dense fluids. Third, the phenomenon of melting has a negligible effect on the short-time dynamics-in marked contrast to the large discontinuities it causes in static properties. Fourth, the measured scattering efficiencies have confirmed recent theoretical estimates for the solid and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(24 citation statements)
references
References 13 publications
0
23
0
1
Order By: Relevance
“…It is well known that this emission is related to the 2co p decay instability at fl c /4. 17 ' 18 The close correlation between the two sets of data clearly supports the view that these two experimental signatures have a common origin in the 2u> p decay instability. Moreover, the threshold intensity of -^2xl0 14 W cm" 2 is in good agreement with that predicted 18 for the 2co p decay instability for typical coronal plasma conditions (T e == 1 keV, and density scale length L == 50 /xm).…”
mentioning
confidence: 63%
“…It is well known that this emission is related to the 2co p decay instability at fl c /4. 17 ' 18 The close correlation between the two sets of data clearly supports the view that these two experimental signatures have a common origin in the 2u> p decay instability. Moreover, the threshold intensity of -^2xl0 14 W cm" 2 is in good agreement with that predicted 18 for the 2co p decay instability for typical coronal plasma conditions (T e == 1 keV, and density scale length L == 50 /xm).…”
mentioning
confidence: 63%
“…Early observations of harmonic and subharmonic emission were reported by Bobin et al 414 in Nd:glass laser-solid target experiments at a 1-lm wavelength. 415 again employing a Nd:glass laser at a 1-lm wavelength, determined the threshold laser intensity for the onset of 3x 0 =2 emission and found it to be consistent with the threshold for the excitation of the TPD instability as given by Jackson 403 and Rosenbluth.…”
Section: Single-beam Experimentsmentioning
confidence: 86%
“…Not until the 1970s, however, did lasers become powerful enough to allow experimental observation of SRS. Bobin et al 414 observed down-scattered light at x 0 =2 using a Nd:glass laser and a solid hydrogen target ( Fig. 10-2), although it was unclear whether this was actually SRS.…”
Section: Stimulated Raman Scattering (Srs)mentioning
confidence: 99%
“…Second-harmonic (2ω) and three-halved harmonic (3ω/2) emissions from a laserproduced plasma on various surfaces have been experimentally studied by many authors since the first observation by Bobin et al [18]. These phenomena are interesting from the viewpoint of nonlinear optics.…”
Section: Generation Of Backscattered 2ω and 3ω/2 Harmonics Of Femtosementioning
confidence: 98%